MYSTICISM IN JAVANESE SHAMANS: Morality toward God (JOURNAL OF INDONESIAN ISLAM, 2021)
This article explains the mystical practices of Javanese shamans (dukun) called wong pinter and analyzes different types of these practices by comparing definitions, actions, and mystical features discussed in various studies. This article uses field studies and in-depth interviews, the data were analyzed based on theories of mysticism. The study shows that the wong pinter also practices mysticism rooted in Islam and manifests in history especially the history of Islamic mysticism in Indonesia in general and in Java in particular. The study finds that the characteristics of shamans mysticism are substantive, non-formalist, and altruistic. This finding supports the view that shamanism is rooted in Islamic mysticism and is open to discourses of mysticism from other religions. This study does not discuss the level of mystical actions nor does it distinguish categories of mystical practices found in many shaman groups.